IMPROVEMENT TO THE MARGINAL COPING FIT of COMMERCIALLY PURE TITANIUM CAST IN PHOSPHATE-BONDED INVESTMENT BY USING A SIMPLE PATTERN COATING TECHNIQUE - Ferreira Pieralini, Anelise Rodolfo; Nogueira, Fabiane; Ribeiro, Ricardo Faria; Adabo, Gelson Luis [UNESP] (Mosby-elsevier, 2012)
Statement of problem. Coatings of zirconite, Y2O3 or ZrO2 on wax patterns before investing in phosphate-bonded investments have been recommended to reduce the reaction layer in titanium castings, but they are not easily obtainable. Spinel-based investments are relatively stable with molten titanium and could be used as coatings to improve the quality of castings made with those investments.Purpose. The purpose of this study was to evaluate the effect of pattern coating with a commercial spinel-based investment before investing in 1 of 3 phosphate-bonded investments on the marginal coping fit and surface roughness of commercially pure titanium castings.Material and methods. Ten square acrylic resin patterns (12 x 12 x 2 mm) per group were invested in the phosphate-bonded investments Rematitan Plus (RP), Rema Exakt (RE), and Castorit Super C (CA) with or without a coating of the spinel-based investment, Rematitan Ultra (RU). After casting, the specimens were cleaned and the surface roughness was measured with a profilometer. Copings for dental implants with conical abutment were invested, eliminated, and cast as previously described. The copings were cleaned and misfit was measured with a profile projector (n=10). For both tests, the difference between the mean value of RU only and each value of the phosphate-bonded investment was calculated, and the data were analyzed by 2-way ANOVA and Tukey's HSD test (alpha=.05). In addition, the investment roughness was measured in bar specimens (30 x 10 x 10 mm), and the data (n=10) were analyzed by 1-way ANOVA and Tukey's HSD post hoc test (alpha=.05).Results. Two-way ANOVA for casting surface roughness was significant because of the investment, the coating technique, and the interaction between variables. One-way ANOVA was performed to prove the interaction term, and Tukey's post hoc test showed that RP with coating had the lowest mean, while RP had the highest. CA with coating was not different from RP with coating or CA without coating. RE with coating was similar to CA, while RE was different from all groups. For coping marginal fit, the 2-way ANOVA was significant for the investment, the coating technique, and the interaction between variables. The interaction was analyzed by1-way ANOVA and Tukey's HSD test that showed no significant difference among the coated groups, which had better marginal fit than the groups without coating. Among the groups without coating, CA had significant lower marginal misfit than RP, while RE was not different from CA and RP. For the investment surface roughness, the 1-way ANOVA was significant. CA and RU were smoother than RE and RP (P<.001).Conclusions. The coating technique improved the quality of castings fabricated with phosphate-bonded investments. (J Prosthet Dent 2012;108:51-57)